Factors That Influence The Work Performance Of Agricultural Instructors In Cultivating Farmer Groups In Sikur District, East Lombok Regency - Pande Komang Suparyana; Aeko Fria Utama FR (Agriwar Journal, 2024)
This research aims to determine the significance of the simultaneous and partial influence of motivation on the performance of agricultural instructors in Sikur District. The number of samples taken in this research was 50 respondents from agricultural extension workers in Sikur District, East Lombok Regency. Meanwhile, data analysis uses multiple linear regression analysis. Based on the results of research that has been carried out, it is found that intrinsic motivation (X1) and extrinsic motivation (X2) have a positive and significant effect on the performance of agricultural instructors in Sikur District, East Lombok Regency. Based on the results of the partial test (t-test), intrinsic motivation and extrinsic motivation have a significant and positive effect on the performance of agricultural instructors in Sikur District, East Lombok Regency. Meanwhile, the variable that more dominantly influences the performance of agricultural instructors in Sikur District, East Lombok Regency is the intrinsic motivation variable (X1) with a calculated t value of 6.904 which is greater than the extrinsic motivation variable. The intrinsic motivation and extrinsic motivation of agricultural extension instructors in Sikur District, East Lombok Regency are currently classified as moderate. So, there is a need for two-way communication between the instructors and the leadership, because with this effort the leadership can find out what the instructors want and vice versa the instructors can provide feedback to the leadership and the organization, namely by showing higher performance.